PENINGKATAN KESADARAN HAK-HAK KONSUMEN PRODUK PANGAN SEBAGAI UPAYA MEWUJUDKAN KEMANDIRIAN KONSUMEN - Chandra Dewi Puspitasari (Jurnal Penelitian Humaniora, 2010)
The research is aimed at getting the highlights of any efforts by the Desperindagkop, Bantul Regency and LPKSM (Indonesian LKY and LBH) as well as any obstructions in enhancing the awareness of food products’ consumers upon their rights. In addition, this research also shows the most effective models to improve the consumers’ awareness upon their rights. This research is a descriptive qualitative research. The data were collected through interviewing and documenting. The technique in deciding the subjects of the research was done by performing the non-probability sampling technique, specifically the purposive sampling and snowball sampling method. The research was done in six months periods in several Bantul’s sub-districts’: Bangunjiwo, Sanden and Kasihan. Then, the inductive analysis technique was applied to analyze the collected data. From the research, the researcher discovers that the Disperindagkop of Bantul has already performed efforts to enhance the awareness of food products’ consumers upon their rights. The efforts are done in several models such as giving limited counseling or radio counseling, publishing the results of observations and surveys, public campaigns, free consultations (personally or via printed medias) and accept any complaints from the consumers. Meanwhile, the Indonesian LBH performs the limited counseling, publications (controlling and surveying the food products and its policies) and consumers’ complaint services. However, there are obstructive cases in performing the efforts. They are the limit of budgets, human resources, medium as well as the unsupportive consumers to the applied efforts. Therefore, the counseling method; the limited counseling method is seen as the most effective one in this program compared to the other methods. The method has its own eminence and role as the society which is in line with the condition of lack of society’s proaction in looking for information.